Social Problems and the Contextual Compromise: Subjectivity, Objectivity, and Knowledge in Everyday Life - Hier, Sean P. (Qualitative Sociology Review, 2019)
This article builds on recent sociological debates about the explanatory importance of claims-making contexts and the continuing challenges associated with subjectivism and objectivism in social problems research. The sociology of knowledge is used to illustrate how the contextual compromise that has sustained social problems theory and method for at least two decades is based on a number of erroneous assumptions about subjectivity and objectivity in the tradition of phenomenological analysis. To strengthen recent discussions about the contextual dimensions of claims-making activities and framing techniques, the article critically assesses the curious neglect and continuing misrepresentation of the sociology of knowledge in constructionist analyses of social problems.